OCCUPATIONAL SAFETY AND HEALTH IN THE HEALTH SECTOR: AN ANALYSIS FROM THE PERCEPTION OF THE WORKERS. - Genny Torcoroma Navarro Claro (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Compliance with occupational health and safety measures is of great relevance for the control and prevention of occupational diseases and accidents in the health sector, requiring greater efforts during the COVID-19 pandemic to minimize the spread of infection in health professionals, their families and the community in which they live. The present research evaluated the workers' perception of the implementation of the occupational health and safety system, comprised of 3 dimensions. A survey was conducted based on entities in the health sector between August 2021 and May 2022, taking into account a sample of 306 workers and a response rate of 100%. It was initially possible to characterize the population, which is made up of 69% women between 18 and 45 years of age and 31% men between 26 and 60 years of age, most of whom have more than 5 years of experience. The discussion oriented to the results allowed to evaluate the perception that workers have of the dimensions of safety and health at work and the different factors that compose it, determining the weaknesses that should be addressed to improve its management, taking into account that the large number of cases of infection by covid-19 in this population could be related to the lack of specific training on the care and use of Personal Protective Equipment - PPE - among other factors.